Regulasi Emosi Secara Kognitif Guru dan Perilaku Antisosial Anak - Yulianto, Dema; Utomo, Hanggara Budi; Kurniawati, Epritha (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2020)
Emotional regulation can be done with cognitive and behavioral approaches. The cognitive approach explains that the emotions felt by individuals are the result of an assessment of the situation they are facing. The research objective was to describe and explore the approach to cognitive-emotional regulation of teachers in dealing with the anti-social behavior of kindergarten children. This research method is a literature study with a qualitative approach. Basically, the literature study is related to theoretical studies and other references related to values, culture, and norms that develop in the situation under study. The role of cognitive-emotional regulation that teachers can do, includes: (1) teachers can teach children's emotional regulation by responding to emotions and teaching about emotions; (2) teachers can provide guidance in emotional competence by giving examples of positive and negative emotions, how to respond to children's emotions, and manifest emotions; (3) teachers can interact with children while identifying emotions that often arise in children